Retroperitoneal hematoma by disruption of renal tissue in the child. - Benedictti, Juan L; Chavarría, Oscar; Falconi, Luis (Cirugía del Uruguay, 1984)
A case of retroperitoneal hematoma by disruption of the renal tissue in the child gives rise to effological, pathologic and therapeutic considerations, pointing out to the importance and severe consequences of this condition.